Birds of Aruba, Bonaire, and Curaçao : a site and field guide - Wells, Jeffrey V. (Jeffrey Vance), 1964-; Wells, Allison Childs (Comstock Publishing Associates, a division of Cornell University Press, 2017)
"A site guide and field guide to the birds of Aruba, Bonaire, and Curaçao. Site guide includes maps, directions, photos, and birds likely to be found. Field guide includes illustrations and describes plumage, similar species, vocalizations, status, and range"--